High-resistivity strontium-doped lanthanum gallium silicate crystal and preparation method thereof

By replacing part of La3+ to Sr2+ in gallium silicate crystals and optimizing the growth conditions by using melt growth method, the problem of low resistivity of gallium silicate crystals is solved, significantly improving its high-temperature resistivity and improving crystal quality.

CN119824541APending Publication Date: 2025-04-15SUZHOU JINGCAI ELECTRONIC TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510075282.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The resistivity of gallium silicate crystals is relatively low, which limits its application in the field of high temperatures.

Method used

By replacing Sr2+ in the LGS crystal, the melt growth method is used to optimize the growth conditions and processes of the crystal to improve the resistivity of the crystal.

Benefits of technology

The high-temperature resistivity of strontium-doped gallium silicate crystals is significantly improved, and the average increase is 3.3 to 15.5 times compared with conventional LGS crystals, and the crystal quality is good and there are no macroscopic defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824541A_ABST
    Figure CN119824541A_ABST
Patent Text Reader

Abstract

The invention discloses a high-resistivity strontium-doped lanthanum gallium silicate crystal and a preparation method thereof.The preparation method comprises the steps that La2O3 powder, SrCO3 powder, Ga2O3 powder and SiO2 powder are mixed according to the molar ratio of (28-30.5): (1-0.05): (50-52): (17-21), then a homogeneous raw material is obtained through wet ball milling, and a polycrystalline material block is obtained through sintering; heating the polycrystal material block until the polycrystal material block is fully melted to obtain a polycrystal melt; and completing crystal growth by adopting a melt growth method. The chemical formula of the obtained strontium-doped lanthanum gallium silicate crystal is La (3-x) SrxGa5SiO14, wherein x is more than or equal to 0.05 and less than or equal to 0.2. The strontium-doped lanthanum gallium silicate crystal provided by the invention has the advantages of good crystallinity, high resistivity, easy growth and the like, and has application prospects in the aspects of high-temperature surface acoustic wave and acoustic bulk wave piezoelectric elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crystal growth, and in particular relates to a high-resistivity strontium-doped lanthanum gallium silicate crystal and a preparation method thereof. Background Art

[0002] Generally, piezoelectric materials with a Curie temperature greater than 400°C are high-temperature piezoelectric materials, which mainly include piezoelectric ceramics and piezoelectric crystals. Among them, piezoelectric crystals have obvious advantages in performance and stability. Currently, the most widely used high-temperature piezoelectric crystals include α-quartz, lithium niobate, tourmaline, gallium phosphate, lanthanum gallium silicate, aluminum nitride, etc. Among them, lanthanum gallium silicate crystals have a series of outstanding advantages and have been widely concerned in high-temperature applications in recent years.

[0003] Langasite crystal (English: langasite, chemical formula: La3Ga5SiO 14 , hereinafter abbreviated as: LGS) is a new type of high-temperature piezoelectric crystal with excellent performance. The electromechanical coupling coefficient (~17%) is about 2~3 times that of quartz. It has a zero-frequency temperature coefficient cut, and there is no phase change from the crystal to the melting point (~1500℃). It has broad application prospects in high-temperature bulk acoustic wave (BAW) and surface acoustic wave (SAW) devices.

[0004] LGS crystal belongs to the trigonal system, 32 point group, P 321 Space group, with A3BC3D2O 14 Configuration, in which there are four different cation sites, ABCD, among which Ga 3+ In addition to completely occupying the B and C sites, it also occupies half of the D site, forming a structurally disordered crystal. This disordered distribution of Ga 3+ This leads to a decrease in crystal resistivity and an increase in dielectric loss. In addition, there are intrinsic defects of oxygen vacancies in the crystal. The lower the concentration of oxygen vacancies (carriers), the smaller the mobility, which causes the resistivity to decrease.

[0005] Chinese invention patent (CN200710173620.5) uses the first principle calculation method to calculate the A3BC3D2O 14 The calculation and screening of similar structure crystals revealed Ca3TaAl3Si2O 14 and Sr3TaAl3Si2O 14 etc., but due to the use of Al 3+ Replaced Ga 3+This results in poor crystallinity and difficulty in growing large-sized single crystals. The Chinese invention patent (CN201310590352.2) discloses chromium, manganese or cobalt doped lanthanum gallium silicate crystals and their melt growth method, which uses relatively cheap Cr, Mn and Co elements to partially replace Ga to improve or overcome the effect of Ga volatilization on crystal quality, but does not mention the high-temperature resistivity performance of the crystal. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem of low resistivity of lanthanum gallium silicate crystals, provide a strontium-doped lanthanum gallium silicate crystal and a preparation method thereof, so as to improve the crystal resistivity, thereby promoting the widespread application of lanthanum gallium silicate crystals in high-temperature fields.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a high resistivity strontium-doped lanthanum gallium silicate crystal comprises the following steps: (1) La2O3 powder, SrCO3 powder, Ga2O3 powder and SiO2 powder are mixed in a molar ratio of 28-30.5:1-0.5:50-52:17-21, and then wet-milled to obtain a homogeneous raw material; (2) sintering the raw material obtained in step (1) to obtain a polycrystalline block; (3) heating the polycrystalline block obtained by sintering in step (2) until it is fully melted to obtain a polycrystalline melt; (4) The crystal growth is completed by using the melt growth method.

[0008] Specifically, in step (1), the purity of La2O3 powder, SrCO3 powder, Ga2O3 powder and SiO2 powder is greater than 4N.

[0009] Specifically, in step (1), the wet ball milling uses zirconium oxide balls and anhydrous ethanol as the mixing medium.

[0010] Specifically, in step (2), the ball-milled raw material is dried, mixed, pressed, and sintered to obtain a polycrystalline block; the sintering temperature is 1350-1450° C., and the calcination is performed for more than 12 hours.

[0011] Specifically, in step (3), the sintered polycrystalline blocks are placed in a crucible in batches and heated to 1500-1600° C. to fully melt the polycrystalline material to obtain a polycrystalline melt.

[0012] Specifically, in step (4), after the polycrystalline melt is kept warm for 2 to 24 hours to stabilize the melt state, any one of the Czochralski method, the descending method, and the zone melting method is used to grow crystals.

[0013] Specifically, in step (4), the melt pulling method is used to complete the crystal growth through seeding, pulling, necking, shoulder release, equal diameter, tailing and annealing.

[0014] Specifically, during the pulling process, a rotation speed of 15 to 30 rpm is used, and the pulling speed is controlled to be 0.5 to 2 mm / h after the start. The growth process includes seeding, diameter reduction, shoulder release, and equal diameter operations.

[0015] Specifically, during the annealing process, the crystal is lifted out of the melt, the rotation rate is uniformly reduced to 5-10 rpm, the crystal is cooled to 1100-1300°C at a rate of 10-30°C / h, maintained for 10-20 hours, and then cooled to room temperature at a rate of 30-180°C / h to obtain a strontium-doped lanthanum gallium silicate crystal.

[0016] Furthermore, the high resistivity strontium-doped lanthanum gallium silicate crystal prepared by the above preparation method is also within the protection scope of the present invention, and the resistivity of the strontium-doped lanthanum gallium silicate crystal at 400°C is ≥1.35×10 8 Ω·cm; resistivity ≥6.54×10 at 500℃ 7 Ω·cm; resistivity ≥1. 26×10 at 600℃ 7 Ω·cm. Beneficial Effects

[0017] The present invention aims to utilize Sr by optimizing raw materials, growth conditions and growth process. 2+ Replace part of La in LGS crystal 3+ The occupancy of Sr-doped LGS crystals improves the problem of low resistivity of LGS crystals without affecting the crystallinity of the crystals. The grown Sr-doped LGS crystals have no macro defects such as inclusions, bubbles, and cracks. Compared with LGS crystals, the resistivity at high temperatures is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0019] Figure 1 This is a photo of the Sr-doped LGS crystal grown by the present invention.

[0020] Figure 2 This is a rocking curve graph of the Sr-doped LGS crystal grown in Example 1 of the present invention.

[0021] Figure 3 This is a comparison chart of the resistivity at high temperature of a conventional LGS crystal and a Sr-doped LGS crystal grown in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The present invention can be better understood with reference to the following examples. Example 1

[0023] La2O3, SrCO3, Ga2O3 and SiO2 powders with a purity of 4N were weighed in a molar ratio of 30.05: 0.05: 52:19, and zirconium oxide balls were added. The mixture was wet-milled in a ball mill with anhydrous ethanol as a mixing medium. The milled raw materials were dried, mixed, pressed and sintered to obtain polycrystalline blocks.

[0024] The sintered polycrystalline blocks are placed in a crucible in batches, placed in a temperature field and heated to 1500°C using a medium frequency power supply. After sufficient heat preservation and melting, the crystals begin to grow; the temperature is lowered to the seeding temperature of 1460°C. During the growth process, the rotation speed of the crystal is controlled to be 15 rpm and the pulling speed is 0.5 mm / h.

[0025] After the equal diameter is completed, the crystal is pulled out of the melt, the rotation speed is uniformly reduced to 5rpm, and the temperature is lowered to 1100℃ at a rate of 10℃ / h. After maintaining for 10 hours, it is cooled to room temperature at a rate of 30℃ / h to obtain a strontium-doped lanthanum gallium silicate crystal with a size of φ75mm×52mm.

[0026] like Figure 1 As shown, the crystals are transparent, without cracks, inclusions or bubbles. Figure 2 The rocking curve spectrum of the Sr-doped LGS crystal grown in Example 1 of the present invention. The half-height width of the rocking curve of the crystal obtained in this example is 31", which has good crystal quality, indicating that Sr 2+ Replaced part of La in LGS crystal 3+ Placeholder. Figure 3 The high temperature resistivity comparison diagram of conventional LGS crystal and Sr-doped LGS crystal grown by the present invention is shown in Figure 1. The resistivity of the 10×10×1 mm wafer of the crystal obtained in this embodiment at 400°C is 1.25×10 9 Ω·cm, resistivity at 500℃ is 1.78×10 8 Ω·cm, resistivity at 600℃ is 5.62×10 7 Ω·cm, which is 15.5 times higher than that of conventional LGS crystals. Example 2

[0027] La2O3, SrCO3, Ga2O3 and SiO2 powders with a purity of 4N were weighed in a molar ratio of 28.9: 0.2: 50.6:18, and zirconium oxide balls were added. The mixture was wet-milled in a ball mill with anhydrous ethanol as a mixing medium. The milled raw materials were dried, mixed, pressed and sintered to obtain polycrystalline blocks.

[0028] The sintered polycrystalline blocks are placed in a crucible in batches, placed in a temperature field and heated to 1600°C using a medium frequency power supply. After sufficient heat preservation and melting, the crystals begin to grow; the temperature is lowered to the seeding temperature of 1475°C. During the growth process, the rotation speed of the crystal is controlled to be 25 rpm and the pulling speed is 1.5 mm / h.

[0029] After the equal diameter is completed, the crystal is pulled out of the melt, the rotation speed is uniformly reduced to 8rpm, and the temperature is cooled to 1100℃ at a rate of 30℃ / h. After keeping for 10 hours, it is cooled to room temperature at a rate of 150℃ / h to obtain a strontium-doped lanthanum gallium silicate crystal with a size of φ82mm×56mm. The crystal is transparent, without cracks, inclusions, and bubbles. The half-height width of the rocking curve of the obtained crystal is 30.3″, which has good crystal quality; the resistivity of the 10×10×1mm wafer of the obtained crystal at 400℃ is 1.41×10 8 Ω·cm, resistivity at 500℃ is 8.92×10 7 Ω·cm, the resistivity at 600℃ is 3.62×10 7 Ω·cm, which is 5.9 times higher than that of conventional LGS crystals. Example 3

[0030] La2O3, SrCO3, Ga2O3 and SiO2 powders with a purity of 4N were weighed at a molar ratio of 29.5: 1: 50:17.5, and zirconium oxide balls were added. The mixture was wet-milled in a ball mill with anhydrous ethanol as a mixing medium. The milled raw materials were dried, mixed, pressed and sintered to obtain polycrystalline blocks.

[0031] The sintered polycrystalline blocks are placed in a crucible in batches, placed in a temperature field and heated to 1580°C using a medium frequency power supply. After sufficient heat preservation and melting, the crystals begin to grow; the temperature is lowered to the seeding temperature of 1475°C. During the growth process, the rotation speed of the crystal is controlled to be 30 rpm and the pulling speed is 2 mm / h.

[0032] After the equal diameter is completed, the crystal is pulled out of the melt, the rotation speed is uniformly reduced to 5rpm, and the temperature is cooled to 1200℃ at a rate of 30℃ / h. After keeping for 10 hours, it is cooled to room temperature at a rate of 180℃ / h to obtain a strontium-doped lanthanum gallium silicate crystal with a size of φ80mm×65mm. The crystal is transparent, without cracks, inclusions, and bubbles. The half-height width of the rocking curve of the obtained crystal is 32.1″, which has good crystal quality; the resistivity of the 10×10×1mm wafer of the obtained crystal at 400℃ is 1.35×10 8 Ω·cm, resistivity at 500℃ is 6.54×10 7 Ω·cm, resistivity at 600℃ is 1.26×10 7 Ω·cm, which is 3.3 times higher than that of conventional LGS crystals.

[0033] Comparative Example La2O3, Ga2O3 and SiO2 powders with a purity of 4N were weighed in a molar ratio of 30.1:50.6:19.3, and zirconium oxide balls were added. The mixture was mixed with anhydrous ethanol and wet-milled in a ball mill. The milled raw materials were dried, mixed, pressed and sintered to obtain polycrystalline blocks.

[0034] The sintered polycrystalline blocks are placed in a crucible in batches, placed in a temperature field and heated to 1500°C using a medium frequency power supply. After sufficient heat preservation and melting, the crystals begin to grow; the temperature is lowered to the seeding temperature of 1460°C. During the growth process, the rotation speed of the crystal is controlled to be 15 rpm and the pulling speed is 0.5 mm / h.

[0035] After the diameter is equalized, the crystal is pulled out of the melt, the rotation speed is uniformly reduced to 5 rpm, and the temperature is lowered to 1100°C at a rate of 10°C / h. After being kept for 10 hours, it is cooled to room temperature at a rate of 30°C / h to obtain a 75mm×60mm lanthanum gallium silicate crystal. The resistivity of the 10×10×1mm crystal at 400°C is 6.3×10 7 Ω·cm, resistivity at 500℃ is 1.41×10 7 Ω·cm, resistivity at 600℃ is 3.98×10 6 Ω·cm.

[0036] The present invention provides a high resistivity strontium-doped lanthanum gallium silicate crystal and a method for preparing the same. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented using existing technologies.

Claims

1. A method for preparing high resistivity strontium-doped lanthanum gallium silicate crystals, characterized in that: The steps include: (1) La2O3 powder, SrCO3 powder, Ga2O3 powder and SiO2 powder are mixed in a molar ratio of 28-30.5:1-0.05:50-52:17-21, and then wet-milled to obtain a homogeneous raw material; (2) sintering the raw material obtained in step (1) to obtain a polycrystalline block; (3) heating the polycrystalline block obtained by sintering in step (2) until it is fully melted to obtain a polycrystalline melt; (4) The crystal growth is completed by using the melt growth method.

2. The method for preparing high resistivity strontium-doped lanthanum gallium silicate crystal according to claim 1, characterized in that: In step (1), the purity of La2O3 powder, SrCO3 powder, Ga2O3 powder and SiO2 powder is greater than 4N.

3. The method for preparing high resistivity strontium-doped lanthanum gallium silicate crystal according to claim 1, characterized in that: In step (1), the wet ball milling uses zirconium oxide balls and anhydrous ethanol as the mixing medium.

4. The method for preparing high resistivity strontium-doped lanthanum gallium silicate crystal according to claim 1, characterized in that: In step (2), the ball-milled raw material is dried, mixed, pressed, and sintered to obtain a polycrystalline block; the sintering temperature is 1350-1450° C., and the calcination is performed for more than 12 hours.

5. The method for preparing high resistivity strontium-doped lanthanum gallium silicate crystal according to claim 1, characterized in that: In step (3), the sintered polycrystalline blocks are placed in a crucible in batches and heated to 1500-1600° C. to fully melt the polycrystalline blocks to obtain a polycrystalline melt.

6. The method for preparing high resistivity strontium-doped lanthanum gallium silicate crystal according to claim 1, characterized in that: In step (4), after the polycrystalline melt is kept warm for 2 to 24 hours to stabilize the melt state, any one of the Czochralski method, the descending method, and the zone melting method is used to grow crystals.

7. The method for preparing high resistivity strontium-doped lanthanum gallium silicate crystal according to claim 1, characterized in that: In step (4), the melt pulling method is used to complete the crystal growth through seeding, pulling, necking, shoulder release, equal diameter, tailing and annealing.

8. The method for preparing high resistivity strontium-doped lanthanum gallium silicate crystal according to claim 7, characterized in that: During the pulling process, a rotation speed of 15-30 rpm is used, and the pulling speed is controlled to be 0.5-2 mm / h after the start.

9. The method for preparing high resistivity strontium-doped lanthanum gallium silicate crystal according to claim 7, characterized in that: During the annealing process, the crystal is removed from the melt, the rotation rate is uniformly reduced to 5-10 rpm, the crystal is cooled to 1100-1300°C at a rate of 10-30°C / h, maintained for 10-20 hours, and then cooled to room temperature at a rate of 30-180°C / h.

10. The high resistivity strontium-doped lanthanum gallium silicate crystal prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The resistivity of the strontium-doped lanthanum gallium silicate crystal at 400°C is ≥1.35×10 8 Ω·cm; resistivity ≥6.54×10 at 500℃ 7 Ω·cm; resistivity ≥1.26×10 at 600℃ 7 Ω·cm.

Citation Information

Patent Citations

  • Piezo crystal having four-lattice structure

    CN101275279A

  • Chromium, manganese or cobalt-doped lanthanum gallium silicate crystal and melt growth method thereof

    CN103603047A